Negative electrode material and preparation method and application thereof

By using N-doped carbon framework and Co3Se4/MoSe2 composite materials as the negative electrode materials of sodium ion batteries, the problems of low specific capacity and poor cycle stability of traditional materials are solved, and the battery performance with high energy density and long cycle life is achieved.

CN119447244APending Publication Date: 2025-02-14CHANGCHUN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411578418.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional sodium ion battery negative electrode materials such as hard carbon cannot meet the market demand for high-energy-density batteries due to their low theoretical specific capacity and poor circulation stability.

Method used

An N-doped carbon skeleton and the Co3Se4/MoSe2 composite material dispersed therein are used as the negative electrode material, and a heterojunction is formed between Co3Se4 and MoSe2, and a MOF-derived carbon material is used as the skeleton to improve porosity and specific surface area.

Benefits of technology

It achieves high specific capacity and excellent electrochemical cycle stability, improving the sodium storage performance and cycle life of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005122387620000101
    Figure BDA0005122387620000101
  • Figure HDA0005122387630000011
    Figure HDA0005122387630000011
  • Figure HDA0005122387630000012
    Figure HDA0005122387630000012
Patent Text Reader

Abstract

The invention relates to the technical field of electrode materials, in particular to a negative electrode material and a preparation method and application thereof. The invention provides a negative electrode material. The negative electrode material comprises an N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton, the N-doped carbon skeleton is an MOF (Metal Organic Framework) derived carbon material; and a heterojunction is formed between the Co3Se4 and the MoSe2 in the Co3Se4 / MoSe2 composite material. The negative electrode material has high specific capacity and excellent electrochemical cycle stability at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a negative electrode material and a preparation method and application thereof. Background Art

[0002] The electrochemical performance of sodium-ion batteries depends largely on the electrode materials. Therefore, regulating the physical and chemical properties of electrode materials can greatly improve the sodium storage performance of batteries. However, traditional sodium-ion battery anode materials (such as hard carbon) can no longer meet the current market demand for high-energy-density batteries due to their low theoretical specific capacity. Therefore, the development of anode materials with larger specific capacity, better cycle performance and higher safety has become the primary goal of the commercial application of sodium-ion batteries.

[0003] Transition metal selenides have unique crystal structures, high specific surface areas and rich oxidation states, which can not only enhance the contact between the electrode and the electrolyte and increase the reaction rate, but also store more charge and increase the theoretical specific capacity. In addition, transition metal selenides can also adapt to the volume change during ion insertion, improve the charge and discharge efficiency, and increase the battery cycle life. Therefore, transition metal selenides are expected to be widely used in sodium ion battery anode materials. Among them, the cobalt-based selenide Co3Se4 has excellent electrochemical properties and has attracted widespread attention. Co3Se4 has a unique crystal structure, which enables sodium ions to be quickly embedded and extracted during the charge and discharge process, significantly improving the charge and discharge efficiency of the battery. At the same time, the cobalt element has a multivalent state characteristic, which enables Co3Se4 to achieve multi-electron transfer in the electrochemical reaction, increase the theoretical specific capacity, and further improve the energy density. However, Co3Se4 also has certain shortcomings as a negative electrode material for sodium ion batteries, such as the gradual decrease in cycle stability in practical applications, resulting in a gradual attenuation of battery capacity. Therefore, comprehensively improving the electrochemical sodium storage performance of Co3Se4 has become the current research focus. Summary of the invention

[0004] The object of the present invention is to provide a negative electrode material and a preparation method and application thereof. The negative electrode material has high specific capacity and excellent electrochemical cycle stability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a negative electrode material, comprising a N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton;

[0007] The N-doped carbon skeleton is a MOF-derived carbon material;

[0008] A heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material.

[0009] Preferably, the mass ratio of the N-doped carbon skeleton to the Co3Se4 / MoSe2 composite material is 1:(1.18-1.38).

[0010] Preferably, the molar ratio of Co to Mo in the Co3Se4 / MoSe2 composite material is (1-5):1.

[0011] The present invention also provides a method for preparing the negative electrode material described in the above technical solution, comprising the following steps:

[0012] ZIF-67, molybdate and solvent are mixed and subjected to ion exchange reaction to obtain CoMo-MOF precursor;

[0013] The CoMo-MOF precursor is placed downstream of the air inlet of the tubular furnace, and the selenium powder is placed upstream of the air inlet of the tubular furnace, and annealing is performed to obtain the negative electrode material.

[0014] Preferably, the molybdate comprises sodium molybdate and / or ammonium molybdate.

[0015] Preferably, the molar ratio of cobalt in the ZIF-67 to molybdenum in the molybdate is (1-5):1.

[0016] Preferably, the solvent includes water and ethanol;

[0017] The volume ratio of water to ethanol is (1-2.3):1.

[0018] Preferably, the ion exchange reaction is carried out under stirring;

[0019] The temperature of the ion exchange reaction is room temperature, and the time is 10 to 14 hours.

[0020] Preferably, the annealing is carried out in a protective atmosphere;

[0021] The annealing temperature is 550-650° C., and the insulation time is 4-8 hours.

[0022] The present invention also provides the use of the negative electrode material described in the above technical solution or the negative electrode material prepared by the preparation method described in the above technical solution in a sodium ion battery.

[0023] The present invention provides a negative electrode material, including an N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton; the N-doped carbon skeleton is a MOF-derived carbon material; a heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material. Co3Se4 has high conductivity and strong metallic properties, but during the charge and discharge process of the sodium ion battery, the cycle stability of Co3Se4 gradually decreases, resulting in the gradual attenuation of the capacity of the negative electrode material of the sodium ion battery. MoSe2 with a two-dimensional layered structure has weak interlayer interactions and is easily absorbed by alkali metal ions (Li + 、Na + and K + etc.), but its semiconductor properties make the battery reaction kinetics process relatively slow. Therefore, the present invention combines Co3Se4 and MoSe2 to solve the problems of Co3Se4 and MoSe2 to a certain extent, give full play to the synergistic effect of Co3Se4 and MoSe2, improve the conductivity of electrode materials, improve ion diffusion kinetics, enhance the mechanical properties and chemical stability of electrode materials, optimize the electrode and electrolyte interface, and achieve the purpose of improving the storage performance of sodium ion batteries and improving the stability of electrochemical cycles. Further, in the heterogeneous structure, the interface between different materials can be used as an active site to promote the electrochemical reaction. At the same time, the present invention uses MOF-derived carbon materials as a skeleton with high porosity and specific surface area, which can provide more electron transmission paths and active sites, and improve the reaction kinetics and electrochemical performance of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD diagrams of the ZIF-67 described in Example 1, the negative electrode material described in Comparative Example 1, and the negative electrode material described in Example 1;

[0025] Figure 2 The Raman graph of the negative electrode material described in Example 1;

[0026] Figure 3 SEM images of the ZIF-67 described in Example 1, the CoMo-MOF precursor described in Example 1, the negative electrode material described in Comparative Example 1, and the negative electrode material described in Example 1;

[0027] Figure 4 This is the EDS element distribution diagram of the negative electrode material described in Example 1;

[0028] Figure 5 TEM and HRTEM images of the negative electrode material described in Example 1;

[0029] Figure 6The sodium ion battery with the negative electrode materials described in Comparative Example 1 and Example 1 at 0.1A·g -1 GCD curves (a) and rate performance curves (b) of the first and fifth cycles at a current density of ;

[0030] Figure 7 The cycle stability curve (a) and EIS curve (b) of the sodium ion battery of the negative electrode materials described in Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0031] The present invention provides a negative electrode material, comprising a N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton;

[0032] The N-doped carbon skeleton is a MOF-derived carbon material;

[0033] A heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material.

[0034] In the present invention, the mass ratio of the N-doped carbon skeleton to the Co3Se4 / MoSe2 composite material is preferably 1:(1.18-1.38). In an embodiment of the present invention, the mass ratio of the N-doped carbon skeleton to the Co3Se4 / MoSe2 composite material may be 1:1.2, 1.2:1.65, 1.8:2.29, 2.4:2.94 or 3.6:4.23.

[0035] In the present invention, the molar ratio of Co to Mo in the Co3Se4 / MoSe2 composite material is preferably (1-5): 1. In an embodiment of the present invention, the molar ratio of Co to Mo in the Co3Se4 / MoSe2 composite material may be 4:1, 1:1, 2:1, 3:1 or 5:1.

[0036] The present invention also provides a method for preparing the negative electrode material described in the above technical solution, comprising the following steps:

[0037] ZIF-67, molybdate and solvent are mixed and subjected to ion exchange reaction to obtain CoMo-MOF precursor;

[0038] The CoMo-MOF precursor is placed downstream of the air inlet of the tubular furnace, and the selenium powder is placed upstream of the air inlet of the tubular furnace, and annealing is performed to obtain the negative electrode material.

[0039] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0040] The present invention mixes ZIF-67, molybdate and a solvent, performs an ion exchange reaction, and obtains a CoMo-MOF precursor.

[0041] In the present invention, the source of ZIF-67 is preferably a commercially available product or prepared.

[0042] In the present invention, when the source of the ZIF-67 is prepared, the preparation method of the ZIF-67 preferably includes the following steps: mixing a cobalt salt solution and a dimethylimidazole solution, stirring, aging, washing and drying in sequence to obtain the ZIF-67.

[0043] In the present invention, the cobalt salt in the cobalt salt solution is preferably cobalt nitrate (Co(NO3)2·6H2O) and / or cobalt chloride (CoCl2·6H2O). When the cobalt salt is two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In the present invention, the solvent in the cobalt salt solution is preferably methanol and / or ethanol. When the solvent is methanol and ethanol, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In the present invention, the concentration of the cobalt salt solution is preferably 0.02-0.04 mol / L, more preferably 0.03 mol / L. In the present invention, the cobalt salt solution is preferably prepared by mixing the cobalt salt and the solvent under stirring. The present invention does not have any special restrictions on the stirring process, and a process well known to those skilled in the art is adopted to ensure that a uniform solution is formed. In an embodiment of the present invention, the preparation of the cobalt salt solution is specifically to add the cobalt salt to the solvent, magnetically stir for 10 minutes, and obtain a cobalt salt solution with a concentration of 0.03 mol / L.

[0044] In the present invention, the solvent in the dimethylimidazole solution is preferably methanol and / or ethanol. When the solvent is methanol and ethanol, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In the present invention, the concentration of the dimethylimidazole solution is preferably 0.07-0.09 mol / L, more preferably 0.08 mol / L. In the present invention, the dimethylimidazole solution is preferably prepared by mixing dimethylimidazole and a solvent under stirring. The present invention does not have any special restrictions on the stirring process, and a process familiar to those skilled in the art can be used. In an embodiment of the present invention, the preparation of the dimethylimidazole solution is specifically to add dimethylimidazole to a solvent, magnetically stir for 10 minutes, and obtain a dimethylimidazole solution with a concentration of 0.08 mol / L.

[0045] In the present invention, the molar ratio of the cobalt salt in the cobalt salt solution to the dimethylimidazole in the dimethylimidazole solution is preferably (2-4): (9-7), more preferably 3: 8. In an embodiment of the present invention, the molar ratio of the cobalt salt in the cobalt salt solution to the dimethylimidazole in the dimethylimidazole solution may be 3: 8.

[0046] In the present invention, the mixing is preferably carried out under stirring, the stirring temperature is preferably room temperature, and the stirring time is preferably 20 to 40 minutes, more preferably 30 minutes. The present invention does not have any special restrictions on the stirring speed, and a speed well known to those skilled in the art is adopted to ensure that the purpose of uniform dispersion is achieved within the above stirring time. In an embodiment of the present invention, the stirring can be stirring at room temperature for 10 minutes.

[0047] In the present invention, the aging temperature is preferably room temperature, the aging is preferably performed under static conditions, and the aging time is preferably 10 to 14 hours, more preferably 12 hours. In an embodiment of the present invention, the aging may be performed at room temperature for 12 hours.

[0048] In the present invention, a coordination reaction occurs between cobalt ions and dimethylimidazole during the aging process.

[0049] After the aging is completed, the obtained precipitate is washed, and the washing method is preferably centrifugal washing, and the detergent used in the centrifugal washing is preferably methanol, and the number of washings is preferably ≥ 1. In an embodiment of the present invention, the number of washings can be 3 times. In the present invention, the drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 60°C; the present invention does not have any special limitation on the time of the vacuum drying, and the time familiar to those skilled in the art can be used and sufficient drying can be ensured.

[0050] In the present invention, the molybdate preferably includes sodium molybdate and / or ammonium molybdate. When the molybdate is sodium molybdate and ammonium molybdate, the present invention has no special limitation on the ratio of the sodium molybdate and ammonium molybdate, and they can be mixed in any ratio.

[0051] In the present invention, the solvent preferably includes water and ethanol, and the volume ratio of the water to the ethanol is preferably (1-2.3):1, more preferably 3:2. In an embodiment of the present invention, the volume ratio of the water to the ethanol may be 3:2.

[0052] In the present invention, the molar ratio of cobalt in the ZIF-67 to molybdenum in the molybdate is preferably (1-5):1, more preferably (2-4):1, and most preferably (3-4):1. In an embodiment of the present invention, the molar ratio of cobalt in the ZIF-67 to molybdenum in the molybdate may be 4:1, 1:1, 2:1, 3:1 or 5:1.

[0053] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.

[0054] In the present invention, the ion exchange reaction is preferably carried out under stirring, the temperature of the ion exchange reaction is preferably room temperature, the time is preferably 10 to 14 hours, more preferably 12 hours. In an embodiment of the present invention, the time of the ion exchange reaction can be 12 hours.

[0055] After the ion exchange reaction is completed, the present invention also preferably includes centrifugal separation and drying performed in sequence; the detergent used in the centrifugal washing is preferably ethanol, and the present invention has no special restrictions on the process of the centrifugal washing, and the process well known to those skilled in the art can be used. In the present invention, the drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 60°C. In an embodiment of the present invention, the centrifugal washing can be centrifugal washing 3 times using ethanol; the temperature of the vacuum drying can be 60°C.

[0056] After obtaining the CoMo-MOF precursor, the present invention places the CoMo-MOF precursor downstream of the air inlet of the tubular furnace, places selenium powder upstream of the air inlet of the tubular furnace, and performs annealing to obtain the negative electrode material.

[0057] In the present invention, the mass ratio of the CoMo-MOF precursor to the selenium powder is preferably (0.2-0.6):1, more preferably 0.4:1. In an embodiment of the present invention, the mass ratio of the CoMo-MOF precursor to the selenium powder may be 0.4:1.

[0058] In the present invention, the annealing is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably a nitrogen atmosphere. The annealing temperature is preferably 550-650°C, more preferably 580-620°C, and most preferably 590-610°C; the holding time is preferably 4-8h, more preferably 5-7h, and most preferably 6h. In the present invention, the heating rate to the annealing temperature is preferably 4-6°C / min, more preferably 5°C / min. In an embodiment of the present invention, the annealing temperature can be 600°C, the holding time can be 6h, and the heating rate can be 5°C / min.

[0059] The present invention also provides the use of the negative electrode material described in the above technical solution or the negative electrode material prepared by the preparation method described in the above technical solution in a sodium ion battery.

[0060] The present invention does not have any special limitation on the application method, and the application method may be carried out by methods well known to those skilled in the art.

[0061] In an embodiment of the present invention, the application method is specifically as follows: according to a mass ratio of 7:1.5:1.5, the negative electrode material, carbon black and sodium carboxymethyl cellulose (or polyvinylidene fluoride) described in the above technical solution are mixed, and water is added and stirred thoroughly to obtain a slurry; the slurry is coated on a copper foil, and vacuum dried at 60°C overnight to obtain a sodium ion battery electrode sheet; button sodium ion batteries are assembled in a glove box filled with argon and with a water oxygen value lower than 0.1ppm, and the model of the button battery is CR2032. The assembly order is positive electrode shell-electrode sheet-diaphragm-sodium sheet-gasket-spring-negative electrode shell; wherein the diaphragm is Celgard2400 film or polyethylene film; the electrolyte used is a 1M NaClO4 solution (the solvent is dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate and ethylene carbonate in a volume ratio of 1:1), and the electrolyte also includes a functional additive (the functional additive includes fluoroethylene carbonate or fluoroethylene carbonate, and the volume percentage concentration of the functional additive in the electrolyte is 3%)

[0062] The negative electrode material provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0063] Example 1

[0064] 3 mmol of cobalt nitrate hexahydrate was added to 100 mL of methanol and stirred magnetically for 10 min to obtain a cobalt salt solution;

[0065] 8 mmol of dimethylimidazole was added to 100 mL of methanol and stirred magnetically for 10 min to obtain a dimethylimidazole solution;

[0066] After adding the dimethylimidazole solution to the cobalt salt solution, stirring at room temperature for 30 minutes, aging at room temperature for 12 hours, pouring out the supernatant after standing, centrifugation washing with methanol for 3 times, and vacuum drying at 60° C. to obtain ZIF-67 purple powder;

[0067] 4 mmol of the purple ZIF-67 powder and 1 mmol of sodium molybdate dihydrate were added to a 50 mL mixed solution of deionized water and ethanol in a volume ratio of 3:2, and magnetically stirred at room temperature for 12 h. The obtained lavender solution was centrifuged and washed 3 times with ethanol to separate the lavender CoMo-MOF precursor precipitate, and vacuum dried at 60° C. to obtain a lavender powder of the CoMo-MOF precursor;

[0068] 2.0 g of selenium powder and 0.8 g of the lavender powder of the CoMo-MOF precursor were placed in two porcelain boats, respectively placed upstream and downstream of the air inlet of the tube furnace, and heated to 600 ° C at a heating rate of 5 ° C / min in a nitrogen protective atmosphere and kept warm for 6 hours to obtain a negative electrode material (including a N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton, a heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material, a mass ratio of the N-doped carbon skeleton to the Co3Se4 / MoSe2 composite material is 1:1.2, and the molar ratio of Co and Mo in the Co3Se4 / MoSe2 composite material is 4:1).

[0069] Example 2

[0070] Refer to Example 1, except that: 4 mmol of ZIF-67 purple powder is replaced by 1 mmol of ZIF-67 purple powder to obtain a negative electrode material (including an N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton, a heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material, the mass ratio of the N-doped carbon skeleton, Co3Se4 in the Co3Se4 / MoSe2 composite material, and MoSe2 in the Co3Se4 / MoSe2 composite material is 1.2:0.65:1, and the molar ratio of Co and Mo in the Co3Se4 / MoSe2 composite material is 1:1).

[0071] Example 3

[0072] Refer to Example 1, except that: 4 mmol of ZIF-67 purple powder is replaced by 2 mmol of ZIF-67 purple powder to obtain a negative electrode material (including an N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton, a heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material, the mass ratio of the N-doped carbon skeleton and the Co3Se4 / MoSe2 composite material is 1.8:1.29:1, and the molar ratio of Co and Mo in the Co3Se4 / MoSe2 composite material is 2:1).

[0073] Example 4

[0074] Refer to Example 1, except that: 4 mmol of ZIF-67 purple powder is replaced by 3 mmol of ZIF-67 purple powder to obtain a negative electrode material (including an N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton, a heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material, the mass ratio of the N-doped carbon skeleton and the Co3Se4 / MoSe2 composite material is 2.4:1.94:1, and the molar ratio of Co and Mo in the Co3Se4 / MoSe2 composite material is 3:1).

[0075] Example 5

[0076] Refer to Example 1, except that: 4 mmol of ZIF-67 purple powder is replaced by 5 mmol of ZIF-67 purple powder to obtain a negative electrode material (including an N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton, a heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material, the mass ratio of the N-doped carbon skeleton and the Co3Se4 / MoSe2 composite material is 3.6:3.23:1, and the molar ratio of Co and Mo in the Co3Se4 / MoSe2 composite material is 5:1).

[0077] Comparative Example 1

[0078] 3 mmol of cobalt nitrate hexahydrate was added to 100 mL of methanol and stirred magnetically for 10 min to obtain a cobalt salt solution;

[0079] 8 mmol of dimethylimidazole was added to 100 mL of methanol and stirred magnetically for 10 min to obtain a dimethylimidazole solution;

[0080] After adding the dimethylimidazole solution to the cobalt salt solution, stirring at room temperature for 30 minutes, aging at room temperature for 12 hours, pouring out the supernatant after standing, centrifugation washing with methanol for 3 times, and vacuum drying at 60° C. to obtain ZIF-67 purple powder;

[0081] 2 g of selenium powder and 0.8 g of the purple ZIF-67 powder were placed in two porcelain boats, respectively placed upstream and downstream of the air inlet of the tube furnace. In a nitrogen protective atmosphere, the temperature was increased to 600 ° C at a heating rate of 5 ° C / min and kept for 6 hours to obtain the negative electrode material (denoted as Co3Se4).

[0082] Test Case

[0083] The ZIF-67 described in Example 1, the negative electrode material described in Comparative Example 1 and the negative electrode material described in Example 1 were subjected to XRD test. The test results are as follows: Figure 1 As shown by Figure 1 It can be seen that the diffraction peak of Co3Se4 described in Comparative Example 1 matches the standard card (CODNo.90112804), proving that the Co3Se4 comparative sample was successfully prepared. In addition, the diffraction peak of the negative electrode material described in Example 1 corresponds one-to-one with the standard cards of Co3Se4 (CODNo.90112804) and MoSe2 (PDF No.20-0757), and there is no diffraction peak of other impurity phases;

[0084] Figure 2 This is the Raman graph of the negative electrode material described in Example 1, at 1345 and 1568 cm -1 The two characteristic peaks nearby belong to the D band and the G band of carbon, respectively, which indicates that the negative electrode material described in Example 1 contains carbon material, which is derived from the derived carbon skeleton formed by high-temperature carbonization of the organic ligand in the CoMo-MOF precursor described in Example 1;

[0085] The ZIF-67 described in Example 1, the CoMo-MOF precursor described in Example 1, the negative electrode material described in Comparative Example 1 and the negative electrode material described in Example 1 were subjected to SEM testing. The test results are as follows: Figure 3 As shown, (a) is the SEM image of ZIF-67 described in Example 1, (b) is the SEM image of the CoMo-MOF precursor described in Example 1, (c) is the SEM image of the negative electrode material described in Comparative Example 1, and (d) is the SEM image of the negative electrode material described in Example 1. Figure 3 As shown in (a), the ZIF-67 has a dodecahedral structure, a smooth surface, and a particle size of about 400 nm. Figure 3 As can be seen from (b), the corners of the dodecahedral structure of the CoMo-MOF precursor in Example 1 are slightly smoothed, presenting a rough microspherical morphology; Figure 3 As shown in (c) and (d), the negative electrode material of Example 1 inherits the morphology of the CoMo-MOF precursor well, and is still a rough microsphere with an average particle size of about 400 nm;

[0086] The negative electrode material described in Example 1 was subjected to EDS element distribution test. The test results are as follows Figure 4 As shown, from Figure 4 It can be seen that the five elements Co, Mo, Se, C and N coexist and are evenly distributed in the negative electrode material described in Example 1. The presence of the C element and the N element further indicates that there is a N-doped carbon skeleton in the negative electrode material described in Example 1;

[0087] The negative electrode material described in Example 1 was subjected to TEM and HRTEM tests. The test results are as follows Figure 5 As shown, (a) is a TEM image of the negative electrode material described in Example 1, and (b) is a HRTEM image of the negative electrode material described in Example 1. Figure 5 (a) It can be seen that the negative electrode material has a rough microspherical morphology, and the particle size is about 400nm, which is consistent with the conclusion of the SEM image; Figure 5 (b) It can be seen that the stripes with a spacing of 0.52nm and 0.66nm in the negative electrode material correspond to (200) of Co3Se4 and (002) of MoSe2, respectively, which indicates that a heterojunction is formed between Co3Se4 and MoSe2.

[0088] The sodium ion battery performance of the negative electrode materials described in Comparative Example 1 and Example 1 was tested using CR2032 button half-cells: constant current charge and discharge (GCD), rate performance and cycle performance at room temperature were characterized using a Xinwei battery tester in the potential window range of 0.01 to 3.0 V. Cyclic voltammetry (CV) curves at different scan rates were tested on an electrochemical workstation (CHI660E). 6 Hz frequency range, electrochemical impedance spectroscopy (EIS) test was performed with an AC signal of 5mV amplitude, where Figure 6 The sodium ion battery with the negative electrode materials described in Comparative Example 1 and Example 1 at 0.1A·g -1 The GCD curves (a) and rate performance curves (b) of the first and fifth cycles are obtained at a current density of Figure 6 As shown in (a), a clear charge and discharge platform can be seen in (a). The first cycle constant current discharge specific capacities of the sodium ion batteries of the negative electrode materials described in Comparative Example 1 and Example 1 are 587 and 933 mA·g, respectively. -1 The constant current discharge specific capacities of the fifth cycle are 306 and 521 mA g -1 Compared with Comparative Example 1, the negative electrode material of Example 1 has a higher discharge specific capacity, which indicates that the negative electrode material of Example 1 has better sodium ion battery performance; Figure 6 As shown in (b), compared with the negative electrode material in comparative example 1, the negative electrode material in example 1 has a higher discharge specific capacity at different current densities and exhibits a relatively stable rate performance; at 0.1 A·g -1 At a current density of , the discharge specific capacity of the negative electrode material described in Example 1 is 521 mA·h·g -1 (5th), at 2A·g -1 At a current density of , the discharge specific capacity of the negative electrode material described in Example 1 is 412 mA·h·g -1 (45th), and when the current density returns to 0.1A·g -1At a current density of , the discharge specific capacity of the negative electrode material described in Example 1 is 544 mA·h·g -1 (51th), showing good stability and reversibility;

[0089] Figure 7 The cycle stability curve (a) and EIS curve (b) of the sodium ion battery of the negative electrode material of Comparative Example 1 and Example 1 are shown in FIG. Figure 7 As shown in (a), compared with the negative electrode material described in Comparative Example 1, at 1A·g -1 At a current density of , the negative electrode material described in Example 1 has a large discharge specific capacity (431 mA·h·g -1 ), at the same time, the negative electrode material solution described in Example 1 has a relatively stable capacity retention rate. After 100 charge and discharge cycles, the discharge specific capacity is 391 mA·h·g -1 The above results show that the negative electrode material described in Example 1 has a relatively stable cycle stability; Figure 7 As can be seen from (b), the charge transfer resistance of the sodium ion battery of the negative electrode materials described in Comparative Example 1 and Example 1 are 19Ω and 97Ω respectively. It can be seen that the negative electrode material described in Example 1 has a faster charge transfer capability, which is beneficial to the reaction kinetics of the sodium ion battery.

[0090] The CR2032 button half-cells prepared from the negative electrode materials of Examples 2 to 5 and Comparative Example 1 were -1 The discharge capacity after the fifth cycle at a current density of is shown in Table 1:

[0091] Table 1 CR2032 button half-cells prepared from the negative electrode materials of Examples 2 to 5 and Comparative Example 1 at 0.1 A·g -1 The discharge capacity after the fifth cycle at a current density of

[0092]

[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode material, characterized in that: A composite material comprising a N-doped carbon skeleton and a Co3Se4 / MoSe2 composite material dispersed in the N-doped carbon skeleton; The N-doped carbon skeleton is a MOF-derived carbon material; A heterojunction is formed between Co3Se4 and MoSe2 in the Co3Se4 / MoSe2 composite material.

2. The negative electrode material according to claim 1, characterized in that The mass ratio of the N-doped carbon skeleton to the Co3Se4 / MoSe2 composite material is 1:(1.18-1.38).

3. The negative electrode material according to claim 1, characterized in that The molar ratio of Co to Mo in the Co3Se4 / MoSe2 composite material is (1-5):

1.

4. The method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: ZIF-67, molybdate and solvent are mixed and subjected to ion exchange reaction to obtain CoMo-MOF precursor; The CoMo-MOF precursor is placed downstream of the air inlet of the tubular furnace, and the selenium powder is placed upstream of the air inlet of the tubular furnace, and annealing is performed to obtain the negative electrode material.

5. The preparation method according to claim 4, characterized in that: The molybdate includes sodium molybdate and / or ammonium molybdate.

6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of cobalt in the ZIF-67 to molybdenum in the molybdate is (1-5):

1.

7. The preparation method according to claim 6, characterized in that: The solvent includes water and ethanol; The volume ratio of water to ethanol is (1-2.3):

1.

8. The preparation method according to claim 4, characterized in that: The ion exchange reaction is carried out under stirring; The temperature of the ion exchange reaction is room temperature, and the time is 10 to 14 hours.

9. The preparation method according to claim 4, characterized in that: The annealing is carried out in a protective atmosphere; The annealing temperature is 550-650° C., and the insulation time is 4-8 hours.

10. Use of the negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared by the preparation method according to any one of claims 4 to 9 in a sodium ion battery.